Telling the Chinese story through the English translation of web literature : A Study of River of Time - Siow, Xin Yi (Nanyang Technological University, 2020)
Chinese web literature has been gaining popularity in China with English translations produced and sparking attention across the globe. The rise of Chinese web literature is so apparent that the Chinese government has proposed that it be used as a form of Chinese cultural output, to tell the “Chinese story”. The advantage that Chinese web literature has over traditional print literature as a medium of Chinese cultural output is apparent as it can be transmitted at a much higher speed via the internet. Through the translation of Chinese web novel, River of Time, this paper aims to draw conclusions in the approach and strategies that can be used to produce English translations of Chinese Socialist web novels that can act as a form of Chinese cultural output. This is done with the help of translation theories such as the skopos theory, the translational action theory, and the visibility of the translator. This paper concludes that text types of text chunks within a text must be clearly categorised in order for relevant translation theories to be employed, while keeping the purpose of translation in mind. The translator should also be more visible than invisible in order to fulfil the purpose of cultural output.